2015
DOI: 10.1590/0103-8478cr20131102
|View full text |Cite
|
Sign up to set email alerts
|

Prednisona e meloxicam no tratamento de ratos submetidos ao trauma agudo da medula espinhal

Abstract: RESUMO O objetivo deste estudo foi investigar o efeito da prednisona e do meloxicam na terapia de ratos submetidos ao modelo experimental de trauma agudo da medula espinhal, induzida pelo cateter de Fogarty 2Fr, mediante a avaliação dos parâmetros de estresse oxidativo, dos testes neurológicos e do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…They showed that meloxicam and MPSS could exhibit antioxidant effects and neuroprotective action, but the necrosis and Wallerian degeneration did not stop in rats that underwent acute SCI compared to the control group. Also, they reported that meloxicam had an antioxidant activity that was more prolonged than the group treated with MPSS, mainly due to decreased catalase activity (Aiello et al, 2015). Similar to our study, they administered meloxicam and MPSS one hour after the spinal cord injury.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They showed that meloxicam and MPSS could exhibit antioxidant effects and neuroprotective action, but the necrosis and Wallerian degeneration did not stop in rats that underwent acute SCI compared to the control group. Also, they reported that meloxicam had an antioxidant activity that was more prolonged than the group treated with MPSS, mainly due to decreased catalase activity (Aiello et al, 2015). Similar to our study, they administered meloxicam and MPSS one hour after the spinal cord injury.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our study, in the report of Hakan, locomotion scores were better in the meloxicamtreated group, probably due to repeated prescriptions, but it was not statistically significant compared to the control group (Hakan et al, 2010). Aiello et al (2015) evaluated the effects of prednisone and meloxicam in treating rats that underwent acute SCI. MPSS and meloxicam treatment groups received MPSS and meloxicam with a dosage of 2 mg/kg, IP, every 24 h for 72 h. The beginning of administering two drugs was 60 minutes after the surgical procedure in all the groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation